Students’ Perceptions of Teaching Writing Using Project-Based Learning Model on the Eleventh-Grade Students at SMA Negeri 1 Baros - Aryanti, Risma Dwi; Santika, Kharisma Dewi; Novira, Helma; Sevhianingrum, Sita; Handayani, Ika; Martini, Annisa (Peneliti.net, 2024)
This study aims to find the eleventh-grade students' positive perspectives concerning the use of the project-based learning model in teaching writing analytical exposition text. To reach its aims, this study employs a qualitative descriptive strategy using a case study technique. The data was gathered through observation and questionnaires. This study's population consisted of eleventh-grade students from SMA Negeri 1 Baros, a public school in Banten province. This research included 63 students from Classes XI MIPA 3 and XI IPS 4. Per the research findings, 86.12% of them had a better knowledge of the concepts and scope of the topics covered. 79.85% of respondents expressed a stronger desire to improve their English writing skills. The concept of writing analytical exposition texts was better understood by 90.3% of respondents. Aside from that, it achieved an 82.23% average positive responses in critical thinking training. It can be concluded that using the project-based learning model in writing instruction influences motivation and interest in learning, academic competence, critical thinking skills, and student-teacher interaction.